2019
DOI: 10.1186/s12885-019-5732-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between high-resolution MRI-detected extramural vascular invasion and tumour microcirculation estimated by dynamic contrast-enhanced MRI in rectal cancer: preliminary results

Abstract: Background To determine whether magnetic resonance imaging (MRI)-detected extramural vascular invasion (mrEMVI) status is associated with quantitative perfusion parameters derived from dynamic contrast-enhanced MRI (DCE-MRI) in rectal cancer. Methods Seventy-two patients with rectal adenocarcinoma who underwent curative surgery alone within 2 weeks following rectal MRI were enrolled in this retrospective study. mrEMVI status was determined based on high-resolution MRI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
6
19
0
Order By: Relevance
“…During tumor progression, tumor cells secrete vascular endothelial factors that increase the permeability of tumor blood vessels and loss of function of cell-cell adhesion molecules, leading to a large interstitial space and resulting in an enlarged EES (35,36); thus, it was not surprising that the Ve value was significantly higher in the EMVI-positive group than in the EMVI-negative group. This result was in agreement with those of Chen et al (23), who reported that MRI-detected EMVI-positive patients exhibited an increased Ve value. Regarding the K trans value, our finding was consistent with a recent study that showed that LVI was correlated with a high K trans value in patients with rectal cancer (35) but contrary to that of Chen et al (23).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…During tumor progression, tumor cells secrete vascular endothelial factors that increase the permeability of tumor blood vessels and loss of function of cell-cell adhesion molecules, leading to a large interstitial space and resulting in an enlarged EES (35,36); thus, it was not surprising that the Ve value was significantly higher in the EMVI-positive group than in the EMVI-negative group. This result was in agreement with those of Chen et al (23), who reported that MRI-detected EMVI-positive patients exhibited an increased Ve value. Regarding the K trans value, our finding was consistent with a recent study that showed that LVI was correlated with a high K trans value in patients with rectal cancer (35) but contrary to that of Chen et al (23).…”
Section: Discussionsupporting
confidence: 94%
“…This result was in agreement with those of Chen et al (23), who reported that MRI-detected EMVI-positive patients exhibited an increased Ve value. Regarding the K trans value, our finding was consistent with a recent study that showed that LVI was correlated with a high K trans value in patients with rectal cancer (35) but contrary to that of Chen et al (23). This may be explained by the different inclusion criteria between our studies.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…High-resolution magnetic resonance imaging (MRI) is the preferred clinical imaging method to evaluate lymph node metastasis of rectal cancer[ 5 ]. Rectal MRI can accurately evaluate the tumor location, tumor stage, invasion depth, extramural vascular invasion (EMVI), and circumferential resection margin[ 6 - 8 ]. Accurate MRI assessment is of great significance to patients with rectal cancer, as it is related to the patients' prognosis[ 9 ].…”
Section: Introductionmentioning
confidence: 99%